Pemberian Nafkah Iddah dan Mut’ah Akibat Pembatalan Nikah karena Murtad - Rofiq, M. Khoirur; Fauzizah, Siti; Najichah, Najichah (Qanun: Jurnal Hukum Keluarga Islam, 2023)
Apostasy in Indonesian marriage law can be the reason for the termination of a marriage through divorce or Fasakh (annulment of marriage) as in 2 decisions of Pengadilan Agama Kendal Nomor 2186/Pdt.G/2019/PA.Kdl dan 1727/Pdt.G/2020/PA.Kdl. Initially, both were divorce cases which were decided by the panel of judges based on the ex officio rights of the judge. Fasakh decision is because one of the husband and wife apostates and determines the iddah and mut’ah expenses. This research includes legal research with a juridical and case approach. The results of this study are (1) Judges use ex officio rights in deciding divorce cases due to apostasy being a marriage phase according to the judge's interpretation in addition to the lack of clarity of marriage marriage law because of apostasy in Indonesian marriage law. (2) The determination of the iddah income due to the marriage phase is analogous to the iddah income due to talak divorce (proposed by the husband) and the wife is not nusyuz. As for the determination of mut’ah living due to apostasy due to apostasy, it is equated with the provisions of mut’ah living due to divorce on the condition that the wife has intercourse and is not nusyuz.